the two lives of Lydia Bird - Silver, Josie (London : Penguin Books, 2020)
Written with Josie Silver?s trademark warmth and wit, The Two Lives of Lydia Bird is a powerful and thrilling love story about the what-ifs that arise at life?s crossroads, and what happens when one woman is given a miraculous chance to answer them. Lydia and Freddie. Freddie and Lydia. They?d been together for more than a decade and Lydia thought their love was indestructible. But she was wrong. On Lydia?s twenty-eighth birthday, Freddie died in a car accident. So now it?s just Lydia, and all she wants is to hide indoors and sob until her eyes fall out. But Lydia knows that Freddie would want her to try to live fully, happily, even without him. So, enlisting the help of his best friend, Jonah, and her sister, Elle, she takes her first tentative steps into the world, open to life?and perhaps even love?again. But then something inexplicable happens that gives her another chance at her old life with Freddie. A life where none of the tragic events of the past few months have happened. Lydia is pulled again and again through the doorway to her past, living two lives, impossibly, at once. But there's an emotional toll to returning to a world where Freddie, alive, still owns her heart. Because there's someone in her new life, her real life, who wants her to stay.
"What if you could live your great love story again?"--Cover.
Keywords: Dreams -- Fiction; Man-woman relationships -- Fiction; Life change events -- Fiction; Traffic accident victims -- Fiction; Death -- Fiction; Grief -- Fiction; Romance fiction